Assessment of the compounds formed by oxidative reaction between p-toluenediamine and p-aminophenol in hair dyeing processes: Detection, mutagenic and toxicological properties - Souza, João Carlos de [UNESP]; Silva, Bianca Ferreira da [UNESP]; Morales, Daniel Alexandre; Umbuzeiro, Gisela de Aragão; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2021)
Previous studies have demonstrated the presence of precursors and coupling agents in wastewater from hair dyeing processes. The complex reaction involved in the oxidation of these compounds can generate extremely hazardous sub-products, leading to an increase in the mutagenicity and toxicity of wastewater. Without proper treatment, this highly toxic wastewater may find its way into the drinking water treatment plant. The present work aimed to investigate the main products generated after the oxidation reaction involving p-toluenediamine (PTD) and p-aminophenol (PAP) – precursors that widely used in the composition of commercial permanent hair dyes, under experimental conditions close to the routine hair dyeing process (in the presence and absence of hydrogen peroxide in ammoniacal medium), using spectroscopic techniques. The study also investigated the mutagenicity and toxicity of the products formed in the hairdressing wash water and conducted detection analysis to determine the presence of the precursors and Bandrowski's Base Derivative (BBD) in samples of wastewater, surface and drinking water using HPLC-DAD and linear voltammetry techniques. Based on this investigation, we identified several PTD and PAP self-oxidation products and eleven sub-products derived from the reaction between PTD and PAP. Assays conducted using Salmonella typhimurium YG1041, with and without activation-induced rat liver metabolism (S9), indicated mutagenicity of the reaction products in concentrations above 10.0 μg μL−1. The concentrations of PTD, PAP, and several reactions and oxidation products of these precursors were detected in wastewater and water samples.
Keywords: Hair dyes; p-Aminophenol; p-Toluenediamine; Toxicity; Wastewater analysis